New university presses in the UK: Accessing a mission. (October 2016) - Lockett, Andrew; Speicher, Lara
Abstract : In the space of just a year, five new university presses were launched in the UK. Although very different in size and stages of development, all but one were launched first and foremost as open access presses, based in or supported by their university's library. Why should there have been such a significant flurry of activity in such a short space of time, and what can the stated objectives and activities of these presses tell us about the current UK scholarly publishing environment? To answer some of those questions, this article looks back to the original mission of the founding university presses, examines the policy and funding environments in which the new presses are operating, looks at overseas developments in recent years for comparison, and concludes with a review of the challenges these young presses face as well as the benefits all university presses, but particularly open access ones, can confer to their institutions.